The Impact of Sensory Marketing on Customer Satisfaction: Evidence from the Refectories of the Universities in Quetta, Balochistan - Gul, Maham; Siddiqui, Furqan Ul-haq; Shahzad, Khuram (ACADEMIA International Journal for Social Sciences, 2025)
Sensory marketing involves enhancing customer satisfaction by triggering their five senses, while customer satisfaction denotes the propensity of customers to remain content with the firm’s offerings. The purpose of this study is to unfold the relationship between sensory marketing and customer satisfaction. The research methodology employed in this study is quantitative, utilizing a self-administered questionnaire to collect data from students at universities in Quetta, Balochistan. A convenience sampling technique was used to collect data from students visiting the university’s cafeteria. The data were analyzed using SPSS software, employing correlation and regression analysis. The study concluded that sensory marketing has a significant positive impact on customer satisfaction; therefore, organizations should benefit from employing sensory marketing techniques to enhance their customers’ experience and satisfaction.